Automatic Classification of Wood Texture using Local Binary Pattern & Fuzzy K-Nearest Neighbor - Mohd Khairuddin, Ismail; Ali, Abuassal; Ali, Abdelrahim; Zainal Abidin, Amar Faiz; Mohamad, Syahrul Hisham; Mutaz, Alsawi; Nordin, Nur Anis; Jaafar, Hazriq Izzuan (scientific.net, 2014)
The price of the wood according to the type of wood. Classification of the woods can be done by studying its texture. This paper introduces Fuzzy k Nearest Neighbor to classify 25 types of wood. The wood’s images have been taken from the Wood Database of the Centre for Artificial Intelligence & Robotics, Universiti Teknologi Malaysia. The features of wood images are extracted using Local Binary Pattern. The results of this paper shows improvement in wood classification compare to the previous literature.